Implementation of Guidance and Counseling in Realizing the Profile of Pancasila Students in Elementary Schools - Ainul Mardiyah; Neviyarni S (MODELING: Jurnal Program Studi PGMI, 2023)
The independent curriculum is a curriculum that contains the profile of Pancasila students in its use. The main characteristics of Pancasila students include faith, devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. These six profiles can be formed through guidance and counseling applied in primary school learning. The purpose of guidance and counseling activities itself is to form students' personalities in accordance with the demands of the independent curriculum applied in the school. This article contains the implementation of guidance and counseling activities conducted at SDN 13 Parit Putus with the aim of realizing the profile of Pancasila students in elementary schools. The results showed that SDN 13 Parit Putus does not yet have experts in the field of guidance and counseling, but the implementation of guidance and counseling has been well integrated in learning and all activities conducted at school, namely routine habituation activities that direct students to become Pancasila students who can apply Pancasila values in everyday life.